The Many Faces of Corruption : Tracking Vulnerabilities at the Sector Level - Campos, J. Edgardo; Pradhan, Sanjay (Washington, DC: World Bank, 2012)
This paper explores the use of prototype road maps to identify corruption vulnerabilities, suggests corresponding warning signals, and proposes operationally useful remedial measures in each of several selected sectors and for a selected sample of cross cutting public sector functions that are particularly prone to corruption and that are critical to sector performance. Numerous technical experts have come together in this effort to develop an operationally useful approach to diagnosing and tackling corruption. The many faces of corruption is an invaluable reference for policymakers, practitioners, and researchers engaged in the business of development.